2023
DOI: 10.1097/hep.0000000000000529
|View full text |Cite
|
Sign up to set email alerts
|

Adequate versus deep response to ursodeoxycholic acid in primary biliary cholangitis: To what extent and under what conditions is normal alkaline phosphatase level associated with complication-free survival gain?

Abstract: Background and Aims: Normal alkaline phosphatase (ALP) levels in ursodeoxycholic acid (UDCA)-treated patients with primary biliary cholangitis (PBC) are associated with better long-term outcome. However, second-line therapies are currently recommended only when ALP levels remain above 1.5 times the upper limit of normal (×ULN) after 12-month UDCA. We assessed whether, in patients considered good responders to UDCA, normal ALP levels were associated with significant survival gains. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Several studies have identified prognostic factors that might influence UDCA response and PBC natural history, such as baseline levels of ALP, gamma-glutamyl transferase and bilirubin, age at diagnosis, ethnicity, gender, presence of advanced fibrosis, pattern of auto-antibodies positivity and overlapping with autoimmune hepatitis [7,16,17,21–27] It would be most interesting if the prediction of UDCA response could be based only on simple pretreatment parameters, such as ALP and age. High baseline ALP level seems to be the strongest predictor of response to UDCA therapy in untreated PBC patients, suggesting that the severity of biliary injury or advanced stages of disease are key determinants of whether choleretic therapy will be effective [7,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have identified prognostic factors that might influence UDCA response and PBC natural history, such as baseline levels of ALP, gamma-glutamyl transferase and bilirubin, age at diagnosis, ethnicity, gender, presence of advanced fibrosis, pattern of auto-antibodies positivity and overlapping with autoimmune hepatitis [7,16,17,21–27] It would be most interesting if the prediction of UDCA response could be based only on simple pretreatment parameters, such as ALP and age. High baseline ALP level seems to be the strongest predictor of response to UDCA therapy in untreated PBC patients, suggesting that the severity of biliary injury or advanced stages of disease are key determinants of whether choleretic therapy will be effective [7,16].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Corpechot et al . demonstrated that adequate response to UDCA by Paris-2 criteria may be not enough for some patients and that additional complication-free survival benefit is obtained after normalization of ALP and bilirubin [17]. As treatment options for PBC continue to increase, it is possible to aspire for normal liver biochemistry for high-risk patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the current issue of H epatology , Corpechot et al quantified the theoretical benefit in terms of complication-free survival gains within a group of patients with PBC who met the binary Paris-II response criteria of an ALP < 1.5 × ULN, AST < 1.5 × ULN, and total bilirubin < ULN 7 . Patients were also required to have had an LSM and, importantly, complications included not only death or LT but also hepatocellular cancer and hepatic decompensation.…”
mentioning
confidence: 99%
“…In the current issue of HEPATOLOGY, Corpechot et al quantified the theoretical benefit in terms of complication-free survival gains within a group of patients with PBC who met the binary Paris-II response criteria of an ALP < 1.5 × ULN, AST < 1.5 × ULN, and total bilirubin < ULN. [7] Patients were also required to have had an LSM and, importantly, complications included not only death or LT but also hepatocellular cancer and hepatic decompensation. Among 1047 patients included with a mean UDCA treatment duration of 7.8 years, there were 15 hepatic decompensation events, 3 HCCs, 5 transplants, and 58 total deaths, but only 16 liver-related deaths.…”
mentioning
confidence: 99%
“…
To the editor, With great interest, we read the article of Corpechot et al, [1] who identify levels of alkaline phosphatase <1.0 × upper limit of normal during therapy with ursodeoxycholic acid as the ideal biochemical response. This is especially true for patients with liver stiffness measurement ≥ 10 kPa and/or age ≤ 62 years with a 10-year complication-free survival gain of more than four years.
…”
mentioning
confidence: 99%